PENGELOLAAN PEMBIAYAAN PENDIDIKAN DI SEKOLAH MENENGAH ATAS (SMA) AL MUTTAQIN KOTA TASIKMALAYA - Siti Fakhirah, Rahil; Mubarok, Husni; Luthfiah Resnasari, Upi (Institut Nahdlatul Ulama Tasikmalaya, 2025)
Education is one of the main pillars in shaping high-quality individuals and societies. One aspect that influences the success and quality of educational institutions is financial management. Thus, several issues arise in this study regarding the process of managing educational financing as well as the supporting and hindering factors in the implementation of educational financing at Al Muttaqin Senior High School in Tasikmalaya City. The objectives of this study are: to understand the management of educational financing and the supporting and hindering factors in the implementation of educational financing at Al Muttaqin Senior High School in Tasikmalaya City. This study employs a qualitative method with data collection techniques include observation, interviews, and documentation. Data analysis is conducted through data collection, data reduction, data presentation, and conclusion drawing. To verify the validity of the data, the researcher uses technique triangulation and source triangulation. The research results indicate that the management of educational financing at Al Muttaqin Senior High School includes the following activities: financial planning activities at Al Muttaqin Senior High School involve the preparation of the School Budget Activity Plan (RKAS) and the development of the school financing budget. The implementation of educational financing includes the receipt and expenditure of funds. The sources of financing at Al Muttaqin Senior High School come from the government, the foundation, and the school committee. Evaluation and accountability are carried out by the school to both internal and external parties. Some supporting factors in the management of educational financing at Al Muttaqin Senior High School include thorough planning and accurate allocation, stable student numbers, competent and experienced administrative staff, and a transparent and accountable reporting system. On the other hand, hindering factors include discrepancies between the education report achievements and the foundation, technical obstacles, and some students experiencing delays in monthly or annual payments.